Using the decentralized and liberalized electricity market microworld (LEMM) As an educational tool - Paşaoğlu, Güzay (Elsevier Sci Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, Oxon, England, 2011)
Decentralized and liberalized electricity market involves a great deal of interdisciplinary concepts, including economic, commercial, environmental and technological issues. Consequently, the system is complicated. Accordingly, nowadays introductory courses focusing on the electricity market dynamics have been added to the curriculum at many universities. However, as the electricity market dynamics are complicated, it is not straightforward for students to understand. A teaching tool to assist students to better understand strategic behaviors in the market is thus in high demand. Due to these reasons, Liberalized Electricity Market Microworld (LEMM), incorporating a system dynamics based simulation model, is developed. The LEMM's contribution to the students learning and understanding of the decentralized and liberalized electricity market dynamics have been explored by organizing game sessions with the LEMM for totally 49 students who participated in "Energy Policy and Planning" course in Bogazici University. The findings obtained from the exploratory study reveal that the students improved their understanding of the liberalized and decentralized electricity market through the game session with the LEMM. In this paper, the general characteristics of the LEMM and the underlying model are presented, the microworlds', particularly the LEMM's potential contribution to learning and teaching is discussed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: liberalized electricity market; Microworld; Simulation; Dynamic Decision-Making; Management Education; Simulations; Feedback; Games; Misperceptions; Behavior; Industry; Risk; Liberal Elektrik Piyasası; Mikro Dünya; Simülasyon; Dinamik Karar Verme; Yönetimi Eğitimi; Simülasyonlar; Geri Bildirim; Oyunlar; Yanlış Algılamalar; Davranış; Sanayi